2021
DOI: 10.1038/s41598-021-86471-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and in silico mutagenesis on the reversible inhibitor-bound SARS-CoV-2 main protease complexes reveal the role of lateral pocket in enhancing the ligand affinity

Abstract: The 2019 novel coronavirus pandemic caused by SARS-CoV-2 remains a serious health threat to humans and there is an urgent need to develop therapeutics against this deadly virus. Recent scientific evidences have suggested that the main protease (Mpro) enzyme in SARS-CoV-2 can be an ideal drug target due to its crucial role in the viral replication and transcription processes. Therefore, there are ongoing research efforts to identify drug candidates against SARS-CoV-2 Mpro that resulted in hundreds of X-ray crys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 89 publications
3
18
0
Order By: Relevance
“…Also, the binding pocket of the enzyme is well defined; the aim of the current study is to identify the crucial residues responsible for complex formation, and thus, employing the monomeric conformation for the investigation is reliable. A similar approach has also been reported in other studies. , Therefore, we believe that the protocol used in this study could provide a rough estimate of binding events with its surrounding residues and is reliable. The resulting M pro –GC-376* complex was again subjected to a second round of minimization following the aforementioned steps.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Also, the binding pocket of the enzyme is well defined; the aim of the current study is to identify the crucial residues responsible for complex formation, and thus, employing the monomeric conformation for the investigation is reliable. A similar approach has also been reported in other studies. , Therefore, we believe that the protocol used in this study could provide a rough estimate of binding events with its surrounding residues and is reliable. The resulting M pro –GC-376* complex was again subjected to a second round of minimization following the aforementioned steps.…”
Section: Methodssupporting
confidence: 60%
“…In light of identifying inhibitors specific to M pro , several attempts have been made in the past by screening chemical databases, mechanistic explorations, and mutational analysis . Nevertheless, the studies conducted by Ma et al have shown that using the fluorescence resonance energy transfer (FRET)-based enzymatic assay, several M pro inhibitors were identified with low- to submicromolar-range binding affinity values (0.030 ± 0.008 to >20 IC 50 in μM).…”
Section: Resultsmentioning
confidence: 99%
“…Outside of these well-studied critical M pro sites, there are additional clusters of mutation-intolerant residues. The R131, D197, N203, D289, and E290 lie at the interface of Domain II and Domain III sandwiched between dimers and make up part of a surface identified by structural modeling as a possible distal drug binding pocket ( Bhat et al, 2021 ; Weng et al, 2021 ; Figure 6b ). Within this cluster, a dynamic salt bridge is formed between R131 located on the loop of Domain II connecting β10–11 of the catalytic pocket, and D289 in the α-helical Domain III that has been reported to contribute to the flexibility and structural plasticity of M pro ( Bhat et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the pyrrolidone moiety is inserted in the S1 pocket, interacting with key residues of the oxyanion loop such as Asn142, Gly143, and Ser144, before undergoing a conformational rearrangement around the 18 ns simulation time mark which allows the carbonyl of the pyrrolidone to establish a hydrogen bond with His163. This interaction has been flagged as a conserved interaction across several deposited structures of non-covalent inhibitors 25 . Moreover, this interaction is conserved across all possible substrate peptide crystal structures, where the interacting group is the sidechain of the Glutamine P1 residue 26 .…”
Section: Resultsmentioning
confidence: 99%